2009
DOI: 10.1007/s11664-009-0858-4
|View full text |Cite
|
Sign up to set email alerts
|

Size and Volume Effects on the Strength of Microscale Lead-Free Solder Joints

Abstract: The fracture behavior of microscale lead-free Sn-3.0Ag-0.5Cu solder joints of different sizes was investigated under quasistatic microtension loading. The experimental results show that the ultimate tensile strength of a joint does not always increase with decreasing thickness-to-diameter ratio (d/t), which is commonly regarded as the dominant factor for mechanical constraint in the joint. A clear joint volume effect on the strength has been found, i.e., the joint's strength increases with decreasing joint vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…Refs. [57][58][59] showed that both the ultimate tensile strength and shear strength of lead-free solder joints increased as the joint volume decreased and/or the joint thickness to width ratio increased, both factors reflecting changes in the degree of solder constraint. This suggests that the application of solder J ci data to the prediction of fracture in actual solder joints requires that a similar degree of constraint be present in the specimen used in the fracture measurement and in the joint being analyzed.…”
Section: Comparison Of Dcb and Arcan Specimens For Fracture Load Predmentioning
confidence: 99%
“…Refs. [57][58][59] showed that both the ultimate tensile strength and shear strength of lead-free solder joints increased as the joint volume decreased and/or the joint thickness to width ratio increased, both factors reflecting changes in the degree of solder constraint. This suggests that the application of solder J ci data to the prediction of fracture in actual solder joints requires that a similar degree of constraint be present in the specimen used in the fracture measurement and in the joint being analyzed.…”
Section: Comparison Of Dcb and Arcan Specimens For Fracture Load Predmentioning
confidence: 99%
“…6 [15,16]. To some degree, the solder thickness or gap used in those studies is the standoff height of BGA joint in this study, and whether this conclusion is suitable to samples subjected to shear loading should be verified.…”
Section: Geometry Effect On the Coefficient Of Stress State Of Bga Somentioning
confidence: 81%
“…So far, previous studies mainly focused on line-type solder joints under tensile loading [11,15,16] and non-standard solder joints (e.g., rectangular and hourglass-like solder joints) under shear loading, researches aimed at the geometry or size effect on the shear behavior of BGA solder joints are still limited, especially for in-depth research based on fracture mechanics and numerical methods. Therefore, in this study, the geometry effect on the mechanical performance and fracture behavior of single micro-scale BGA structure Cu/Sn-3.0Ag-0.5Cu/ Cu solder joints under shear loading is characterized by experimental method and 3D finite element (FE) analysis based on the framework of linear elastic and nonlinear fracture mechanics as well as interfacial fracture mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…The most common literature reports presented the typical approach to experimental micro tensile test [4][5][6], in which the strain-stress curves and the SEM micro photographs of specimens were obtained, for example Sn-3.0Ag-0.5Cu solder joints in [4], Ti-base and Cr-base coatings in [5] and TiN-coated steel in [6].…”
Section: Introductionmentioning
confidence: 99%